Nursing students' experiences of what influences achievement of learning outcomes in a problem‐based learning context: A qualitative descriptive study - Jenny Svensson; Anna Axén; Ewa K. Andersson; Markus Hjelm (Wiley, 2021)
Abstract Aim This study aimed to describe nursing students' experiences of what facilitate or impede the achievement of learning outcomes in PBL‐based nursing education. Design A qualitative descriptive design was used. Methods Data were collected from individual semi‐structured interviews with 18 undergraduate nursing students in Sweden and were analysed using Burnard's qualitative content analysis. Results The results were organized into three categories: (a) understanding of the required level of knowledge depth (b) tutor's engagement and (c) student base group interactions. These categories represent essential components of PBL that could either facilitate or impede students' achievement of learning outcomes in nursing education. To improve the students' opportunities to achieve the learning outcomes, proper introduction of and a continuous education on PBL as a pedagogical method provided both to students and tutors should be considered important.